IMPLEMENTATION OF BIM-TECHNOLOGIES IN RUSSIAN CONSTRUCTION INDUSTRY ACCORDING TO THE INTERNATIONAL EXPERIENCE - Ginzburg, Alexander; Shilova, Liubov; Adamtsevich, Aleksey; Shilov, Leonid (Journal of Applied Engineering Science, 2016)
This article considers the main stages of life cycle of construction project’s informational model.  The main trends of using various constructions’ informational models are revealed and the domestic and foreign experience of implementing BIM technology is analyzed. The maturity levels of BIM technologies are considered according to the Bew Richards model of BIM implementation. It helps to make an analysis of currently used software.
Keywords: information model; Life cycle of construction project’s informational model; BIM-technologies